Self Injury : Faktor dan Dampak Psikologis Pada Dewasa Awal (Gen-Z) - Shofia, Asra; Zahroh, Siti Nur Alya; Komalasari, Shanty (Universitas Negeri Surabaya, 2024)
Non-Suicidal Self-Injury (NSSI) is an act of self-harm committed by individuals without the intention to end their lives. Self-injury, a behavior that can have a significant psychological impact on early adult individuals. This study aims to deepen the understanding of the trigger factors and psychological impacts experienced by early adult individuals who commit selfinjury. The purpose of this study is to analyze the factors and impact of self-injury psychology and explore how self-injury relates to family and environmental factors. This study used a qualitative approach with semi-structured interviews. The subjects in this study were three early adult women aged 20 years who experienced self-injury behavior. This study results that the factors that trigger self-injury include loneliness, broken home, strict parents, problems arising from the family, communication with parents, social environment, response to problems. Study subjects described feelings of relief and decreased tension as a positive impact, but also experienced anxiety and addiction as a negative impact of self-injury behavior.